Effectiveness of paitan compost (Tithonia diversifolia) dosages on the growth and biomass of robusta coffee (Coffea canephora L.) seedlings - Yuliatri Yuliatri; Sholeh Riyansyah; Rita Erlinda; Giska Oktabriana (Faculty of Agriculture, Universitas Malikussaleh, 2026)
This study aimed to evaluate the effects of various paitan compost (Tithonia diversifolia) dosages on the growth and biomass of robusta coffee (Coffea canephora L.) seedlings and to determine the most effective dosage during the nursery phase. The research was conducted from March to June 2026 at the Experimental Farm of Politeknik Pertanian Negeri Payakumbuh, West Sumatra. The study employed a Completely Randomized Design (CRD) with five treatments of paitan compost dosages, namely 0, 100, 120, 140, and 160 g/polybag, each replicated five times. The parameters observed included seedling height, number of leaves, leaf length, leaf width, leaf area, fresh weight, and dry weight. The results showed that paitan compost significantly affected the number of leaves, leaf length, and fresh weight of seedlings, but did not significantly affect seedling height, leaf width, and dry weight. The highest number of leaves was obtained at the dosage of 120 g/polybag (10.07 leaves), while the highest leaf length and estimated leaf area were obtained at the dosage of 140 g/polybag, reaching 17.21 cm and 76.20 cm², respectively. The highest fresh weight (1.83 g) and dry weight (0.7440 g) were obtained at the dosage of 100 g/polybag. Dosages of 120–140 g/polybag tended to enhance vegetative growth, whereas 100 g/polybag was more effective at increasing seedling biomass. Based on biomass parameters as indicators of seedling quality, the dosage of 100 g/polybag is recommended for robusta coffee nursery. Paitan compost has the potential to be utilized as an organic nutrient source to support the sustainable growth of robusta coffee seedlings.